PENGARUH LATIHAN UNDER THE BASKET SHOT DENGAN RINTANGAN TERHADAP KEMAMPUAN SHOOTING PERMAINAN BOLA BASKET PADA TIM PUTRA SMP DHARMA LOKA PEKANBARU - Mesianna Simbolon; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem with this research it still a lack of mastering techniques under the basket shot. in addition, athletes also often incorrectly take into the angle of the ball on the basketball throw so the ball more often just pass over the opponent basketball ring. The study research to determine whether there is effect of under the basket shot with an obstacle training on basketball shooting ability of game on the men’s team the middle school first Dharma Loka Pekanbaru. Type of research used is experiment and using one preetest-posttest disign. Population is research in Men’s Team The Middle School First Dharma Loka Pekanbaru is the entire populations of 10 people. While the sample technique used is total sampling (saturated sample) where all the population is sampled. The sample in this study amounted to 10 people of Men’s Team The Middle School first Dharma Loka Pekanbaru. The instruments use in this research is to test basketball shooting for 30 seconds. After that, the data is processed with statistics, normality test with lilifors test at significance level ɑ (0.05). The hypothesis is the effect of under the basket shot with an obstacle exercises on the basketball shooting ability of game in men’s team the middle school first Dharma Loka Pekanbaru. Based on the analysis of statistical data, there are an average pree-test 7,50 and an average post-test 12,80, then the data is normal with an increase of 5.30 . Based on t test analysis produces t hitung = 6.184 > t tabel = 1.833. Meaning t hitung > t tabel. Thus, there effect of exercise under the basket shot with an obstacle of men’s team middle school first Dharma Loka Pekanbaru on basketball ability shooting of men’s team middle school first Dharma Loka Pekanbaru.Keywords: Under The Basket Shot With An Obstacle, Shooting Ability, Basketball